2016
DOI: 10.1186/s41200-016-0096-4
|View full text |Cite
|
Sign up to set email alerts
|

Zonation patterns, composition and diversity of macroalgal communities in the eastern coasts of Qeshm Island, Persian Gulf, Iran

Abstract: This study investigates the spatial and temporal variation of intertidal macroalgae along the eastern coasts of Qeshm Island, Persian Gulf, Iran. Monthly sampling of abundance, biomass, richness and diversity of macroalgae at three intertidal levels was carried out at two different sites during 1 year. The samples were collected every month using quadrats (0.5 × 0.5 m) from October 2012 to September 2013. The species dry weight was applied to examine changes in biomass and assemblage composition of intertidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
5
1
2
Order By: Relevance
“…Although sampling was done for only three months. In contrast to other studies done elsewhere, which showed temporal variation (Tribollet & Vroom, 2007;Mendoza & Soliman, 2013;Kokabi et al 2016), the present study do not. The homogeneity of the environmental variables may have also accounted for this result.…”
Section: Discussioncontrasting
confidence: 99%
“…Although sampling was done for only three months. In contrast to other studies done elsewhere, which showed temporal variation (Tribollet & Vroom, 2007;Mendoza & Soliman, 2013;Kokabi et al 2016), the present study do not. The homogeneity of the environmental variables may have also accounted for this result.…”
Section: Discussioncontrasting
confidence: 99%
“…Hypnea musciformis is a red macroalgae belonging to the Cystocloniaceae family. It is fast-growing opportunistic seaweed that dominated the macroalgal communities in some eastern coasts of Qeshm Island from April to May (Kokabi et al 2016). This species is a carrageenan yielding seaweed commercially cultivated throughout the world (Vadlapudi and Amanchy 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Padina terdistribusi secara luas di perairan tropis dan subtropis [46]. Genus tersebut merupakan kelompok yang paling umum ditemukan di lingkungan perairan dan menjadi spesies dominan [51][52] [53] dan selalu dapat ditemukan di semua musim [54]. Jenis Padina memiliki holdfast yang menyerupai cakram sehingga mampu menempel pada substrat keras dan dapat bertahan di perairan dengan kondisi arus dan gelombang kuat [55].…”
Section: Hasil Dan Pembahasan Komposisi Jenis Makroalgaunclassified
“…Di Kalimantan Barat, Sargassum banyak ditemukan di perairan Pulau Lemukutan [12], Pulau Kabung [10][31], Singkawang [63], Pulau Temajok Kabupaten Mempawah. Keberadaan dan kelimpahan makroalga sangat berkaitan erat dengan kondisi lingkungan perairan [64], seperti musim [51][65] [66], kedalaman [67], suhu [36], dan karakteristik substrat dasar [35][68].…”
Section: Gracilariaunclassified